Is lysate-based human leukocyte antigen crossmatch a reliable method to contraindicate a transplant? - Shruti Tapiawala; Suchita Jogale; Bharat V Shah; Anuradha Raman (Indian Journal of Transplantation, 2023)
The presence of preformed cytotoxic donor-specific antibodies (DSAs) has been associated with inferior allograft outcomes in the immediate posttransplant period. Since the 1970s, the primary method for determining the presence of DSAs has been the complement-dependent cytotoxicity crossmatch. Solid phase assays on the Luminex platform were introduced in India in 2010 in the form of human leukocyte antigen antibody screening, single antigen bead (SAB) assay and lysate-based crossmatch (LumXM) to identify low titer antibodies, which are deleterious to allograft. Instead of SAB, LumXM has been popularly used in India to identify DSAs and also called DSA crossmatch, which is not recommended or validated in International literature for denying or accepting to transplant a patient due to its fallacies. We are reporting three cases which showcase the flawed nature of this test and the implications of this test on day to day practice in transplantation.